Randomised Clinical Efficacy Trial of Topiramate and Nitrazepam in Treatment of Infantile Spasms - FALLAH, Razieh; SALOR, Fahimah; Akhavan Karbasi*, Sedighah; Motaghipisheh, Hadi (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Fallah R, Salor F, Akhavan Karbasi S, Motaghipisheh H. Randomised Clinical Efficacy Trial of Topiramate and Nitrazepam in Treatment of Infantile Spasms. Iran J Child Neurol. 2014 Winter; 8(1):12-19. Objective Infantile spasms (IS) are among the most catastrophic epileptic syndromes of infancy. The purpose of this study was to compare efficacy and safety of topiramate (TPM) and nitrazepam (NZP) as first-line drugs in the treatment of IS. Materials & Methods In a parallel single-blinded randomized clinical trial, 50 patients with IS referred to Pediatric Neurology Clinic of Shahid Sadoughi University of Medical Sciences, Yazd, Iran, were evaluated from September 2008 to March 2010. Patients were randomly assigned to two groups to be treated with TPM or with NZP for 6 months. The primary endpoint was efficacy in cessation of all spasms or reduction of more than 50% in weekly seizure frequency, which was evaluated before and 6 months after the drug use. Secondary outcome was clinical sideeffects of the drugs. Results Twenty boys (40%) and 30 girls (60%) with the mean age of 9.4±3.8 months were evaluated. Cessation of all spasms occurred in 12 (48%) infants in TPM group and 4(16%) in NZP group. Eight (32%) children in TPM group and 7 (28%) in NZP group had more than 50% reduction in spasms frequency. So, TPM was more effective. Side effects were seen in 32% of TPM and in 36% of NZP groups. Conclusion Topiramate is an effective and safe drug, which might be considered as the firstline drug for the treatment of ISs. References: Watemberg N. Infantile spasms: treatment challenges. Curr Treat Options Neurol 2012;14(4):322-31. Tsao CY. Current trends in the treatment of infantile spasms. Neuropsychiatr Dis Treat 2009;5:289-99. Sankar R, Koh S, Wu J, Menkes JH. Paroxysmal disorders. In: Menkes JH, Sarnat HB, Maria BL, editors Child Neurology,7th ed. Philadelphia: Lippincott; 2006.p. 877. Engel J Jr. International League against Epilepsy (ILAE). A proposed diagnostic scheme for people with epileptic seizures and with epilepsy: a report of the ILEA task force on classification and terminology. Epilepsia 2001; 42(6):796–803. Riikonen RS. Favourable prognostic factors with infantile spasms. Eur J Paediatr Neurol 2010;14(1):13-18. Lagae L, Verhelst H, Ceulemans B, De Meirleir L, Nassogne MC, De Borchgrave V, et al. Treatment and long term outcome in West syndrome: the clinical reality. A multicentre follow up study. Seizure 2010;19(3):159-64. Fois A. Infantile spasms: review of the literature and personal experience. Ital J Pediatr 2010;36:15-21. Jaseja H. Justification of vigabatrin administration in West syndrome patients? Warranting a re-consideration for improvement in their quality of life. Clin Neurol Neurosurg 2009;111(2):111-14. Hwang H, Kim KJ. New antiepileptic drugs in pediatric epilepsy. Brain Dev 2008,30(9);549–55. Mikaeloff Y, de Saint-Martin A, Mancini J, Peudenier S, Pedespan JM, Vallée L, et al. Topiramate: efficacy and tolerability in children according to epilepsy syndromes. Epilepsy Res 2003;53(3):225-32. Peltzer B, Alonso WD, Porter BE. Topiramate and Adrenal-Cortico-tropic Hormone as Initial Treatment of Infantile Spasms. J Child Neurol 2009;24(4):400-5. Zou LP, Lin Q, Qin J, Cai FC, Liu ZS, Mix E. Evaluation of open-label topiramate as primary or adjunctive therapy in infantile spasms. Clin Neuropharmacol 2008;31(2):86-92. Korinthenberg R, Schreiner A. Topiramate in children with west syndrome: a retrospective multicenter evaluation of 100 patients. J Child Neurol 2007;22(3):302-6. 14. Kwon YS, Jun YH, Hong YJ, Son BK. Topiramate monotherapy in infantile spasm. Yonsei Med J 2006;47(4):498-504. Hosain SA, Merchant S, Solomon GE, Chutorian A. Topiramate for the treatment of infantile spasms. J Child Neurol 2006;21(1):17-9. Glauser TA, Clark PO, McGee K. Long-term response to topiramate in patients with West syndrome. Epilepsia 2000;41(Suppl. 1):S91-4. Albsoul-Younes AM, Salem HA, Ajlouni SF, Al-Safi SA. Topiramate slow dose titration: improved efficacy and tolerability. Pediatr Neurol 2004;31(5):349-52. Hsieh MY, Lin KL, Wang HS, Chou ML, Hung PC, Chang MY. Low-dose topiramate is effective in the treatment of infantile spasms. Chang Gung Med J 2006;29(3):291-6. Auvichayapat N, Tassniyom S, Treerotphon S, Auvichayapat P. Treatment of infantile spasms with sodium valproate followed by benzodiazepines. J Med Assoc Thai 2007;90(9):1809-14. Karvelas G, Lortie A, Scantlebury MH, Duy PT, Cossette P, Carmant L. A retrospective study on aetiology based outcome of infantile spasms. Seizure 2009;18(3):197-201. Chen CC, Chen TF, Lin HC, Oon PC, Wu HM, Wang PJ, et al. Estimation of prevalence and incidence of infantile spasms in Taiwan using capture–recapture method. Epilepsy Res 2004;58(1):37–42. Parisi P, Bombardieri R, Curatolo P. Current role of vigabatrin in infantile spasms. Eur J Paediatr Neurol 2007;11(6):331-6. Cvitanović-Sojat L, Gjergja R, Sabol Z, Hajnzić TF, Sojat T. Treatment of West syndrome. Acta Med Croatica 2005;59(1):19-29. (Full text in Croatian) Watemberg N, Goldberg-Stern H, Ben-Zeev B, Berger I, Straussberg R, Kivity S, et al. Clinical experience with open-label topiramate use in infants younger than 2 years of age. J Child Neurol 2003;18(4):258-62. Grosso S, Franzoni E, Iannetti P, Incorpora G, Cardinali C, Toldo I, et al. Efficacy and safety of topiramate in refractory epilepsy of childhood: long-term follow-up study. J Child Neurol 2005;20(11):893-7. Capovilla G, Beccaria F, Montagnini A, Cusmai R, Franzoni E, Moscano F, et al. Short-term nonhormonal and nonsteroid treatment in West syndrome. Epilepsia 2003;44(8):1085-8. Chamberlain MC. Nitrazepam for refractory infantile spasms and the Lennox-Gastaut syndrome. J Child Neurol 1996;11(1):31-4. 28. Hosain SA, Green NS, Solomon GE, Chutorian A. Nitrazepam for the treatment of Lennox-Gastaut syndrome. Pediatr Neurol 2003;28(1):16-9. Rintahaka PJ, Nakegawa JA, Shewmom DA, Kyynnem P, Shields WD. Incidence of death in patients with intractable epilepsy, during nitrazepam treatment. Epilepsia 1994;40(4):492-6. Djurić M, Marjanović B, Zamurović D. West syndrome--new therapeutic approach. Srp Arh Celok Lek 2001;129(Suppl.1):72-7. (Full text in Serbian)